Perception Students Of Pkk Study Program Concentration Of Tata Boga About Online Snacks - Hatista, Radhesa; Elida, Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This study aims to describe: Students' perceptions about online snacks as a whole, and based on research indicators. This type of research is descriptive quantitative research. The population of the study consisted of 405 students from the PKK Study Program Concentration of Culinary Art with a total sample of 80 people who were taken based on the total sampling technique. The data sources are students in the 2017-2020 year of entry. The research data collection technique was carried out using a questionnaire designed based on a Likert scale and had been tested for validity and reliability. The data analysis technique was carried out by determining the frequency of data distribution and data classification techniques based on the calculation of scores using the research formula of ideal average (Mi) and standard deviation (Sdi). The results of this study illustrate: Students' perceptions about online snacks as a whole are in the moderate category, based on three research indicators, namely the occurrence of stimulation of the senses (knowledge and general information about snacks) in the high category, stimulation of the senses is regulated (understanding of snacks and snacks with online purchases) and interpreted-evaluated sensory stimulation (assessments of understanding snacks and snacks with online purchases) were in the moderate category. Based on the results of the study, it can be concluded that students of PKK Study Program with a Concentration of Tata Boga have a moderate perception of the subject.